Pelatihan Pengaplikasian Antibakteri dari Ekstrak Daun Jambu Biji pada Pakaian Anak untuk Orang Tua Murid dan Guru – Guru PAUD Bambim Al Muttaqien - Filly Pravitasari; Luciana Luciana; Feny Nurherawati; Afriani Kusumadewi; Susi Maulinawati (Universitas Insan Cendekia Mandiri, 2026)
Children with high levels of activity tend to sweat easily, which results in their clothes quickly becoming wet with sweat, so the clothes they wear can become a good medium for bacterial growth. To overcome the above problems, innovations in antibacterial materials in textiles have been developed, namely by adding antibacterials to fabric fibers. This material is added to the surface of the fabric with the aim of inhibiting the growth of microorganisms. Some natural ingredients that are widely used for fabrics include garlic extract, cloves, bamboo, mahogany, olive leaf extract, ginger and seed leaf extract. The existence of guava leaves used in this community service activity is because the leaves are easy to obtain and are already known by the people in Indonesia. Guava leaves contain compounds such as tannins which have the effect of shrinking the walls of bacteria so that they interfere with the permeability of the cells. This Community Service Activity aims to provide knowledge and insight to the community about the application of antibacterial substances derived from natural ingredients and plants around us. The stages of this activity were firstly the selection of a location that was a partner of UICM, then continued with the optimization of the guava extract recipe which was tested in the UICM laboratory first, after that the preparation of materials and equipment for the PkM activity itself until finally it was carried out according to the expected plan. Community service activities took place with enthusiastic participants involved in the application of guava leaf extract as an antibacterial. This activity received an enthusiastic response and had a positive impact by increasing knowledge, skills and insight for participants of the activity regarding the importance of family health by providing antibacterial protection for children's clothing in particular.